(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
This study discusses the views reviewed in the news published by Suluh Indonesia and Indonesia Raya newspapers. This research uses a historical method which consists of four steps of research: heuristics, criticism, interpretation, and historiography. This study also uses a multidisciplinary approach by taking the concept of newspapers, editorials, corner notes and caricatures in an effort to discuss the research themes raised. Based on the results of the study, the Suluh Indonesia and Indonesia Raya newspapers have different views in viewing Ali Sastroamidjojo II cabinet policy. The Suluh Indonesia newspaper always supported what Ali Sastroamidjojo did, this is because the Suluh Indonesia newspaper is a media organ of the Indonesian National Party, and Ali Sastroamidjojo is a member of the party. So when serving as Prime Minister Ali Sastroamidjojo apart from criticism of this newspaper. In contrast to the Indonesia Raya newspaper, this newspaper always criticizes the policies issued by the Ali Sastroamidjojo II Cabinet, this is because the Indonesia Raya newspaper is classified as an Independent Press which if a policy is not in accordance with the idealism of the Editor in Chief then the newspaper is not will stop criticizing. Moreover, this Independent newspaper has an impartial view of the press into any political power, avoids biased reporting and benefits one party and harms the other party.